Efektivitas Program CSR/CD dalam Pengentasan Kemiskinan; Studi Peran Perusahaan Geotermal di Jawa Barat - Prayogo, Dody; Hilarius, Yosef (UI Scholars Hub, 2012)
This study discusses model of measurement to assess the effectiveness of programs of corporate social responsibility (CSR) held by corporation of mines, oil and gas, and geothermal in relation with poverty alleviation within the surrounding communities. The case study is conducted in a geothermal company in West Java. Results of study indicate that measurements of CSR should be developed in accordance with the scale of program, and should as well make use micro indicators which are relevant with elements of poverty. Also, the assessment should mainly be focused to the target group of beneficiaries. The role of corporation can be differentiated with the role of government in alleviating the poverty, and hence the effectiveness should be measured with micro indicators. In general, the significances of CSR program in poverty alleviation are high in the variables of effectivity and relevance, but low in variables of sustainability and empowerment. Programs of economic and infrastructure development are predominant than that other programs such as education and health.